Effect of Coriander Seeds (Coriandrum Sativum) on Wool Growth and It's Traits and Some Haematological Traits of Awassi Ewes - AL-Zwein, Drgham H. Yousif (The Iraqi Journal of Veterinary Medicine, 2010)
This study was conducted to find out the effect of coriander seeds as feed additive on some hematological traits and wool growth and it's physical traits of Awassi ewes, blood samples were taken biweekly for blood picture, and wool samples were taken every 2.5 months for wool growth and its physical traits. Eighteen Awassi ewes at the age of 2-3 years were randomly divided equally into three groups (6each ) "body weight was considered".Ewes in the first group kept as control and daily fed on concentrate diet (350 g/ head), while the second group was fed on the same diet contain (2.5%) of coriander seeds, while the third group was fed on same diet contain (5%) of coriander seeds. Also all animals were allowed to graze. Blood samples were taken from jugular vein for blood traits viz (PCV) packed cell volume, (Hb) hemoglobin, (MCHC) mean cell hemoglobin concentration. Wool samples (5×5) cm2 were clipped from the last six ribs of the right chest for measuring wool growth and its traits (creasy and clean wool, samples weights, clean wool ratio, staple and fiber lengths and diameters and wool fiber crimps in 1cm of length). The results of blood parameters revealed that the second and third groups were significantly (p<0.05) recorded higher values in their PCV ,Hb, MCHC during most studied periods compared with the control group ,While the second and third groups were significantly (P<0.05) recorded higher values than the first group (control) in their creasy and clean wool, fiber length, wool fiber crimps, while no differences where existed in other wool physical traits.